Transcriptional and post-translational changes in the brain of mice deficient in cholesterol removal mediated by cytochrome P450 46A1 (CYP46A1) - Mast, Natalia (PLoS One, 2017)
Cytochrome P450 46A1 (CYP46A1) converts cholesterol to 24-hydroxycholesterol and thereby controls the major pathways of cholesterol removal from the brain. Cyp46a1(-/-) mice have a reduction in the rate of cholesterol biosynthesis in the brain and significant impairments to memory and learning. To gain insights into the mechanisms underlying Cyp46a1(-/-) phenotype, we used Cyp46a1(-/-) mice and quantified their brain sterol levels and the expression of the genes pertinent to cholesterol homeostasis. We also compared the Cyp46a1(-/-) and wild type brains for protein phosphorylation and ubiquitination. The data obtained enable the following inferences. First, there seems to be a compensatory upregulation in the Cyp46a1(-/-) brain of the pathways of cholesterol storage and CYP46A1-independent removal. Second, transcriptional regulation of the brain cholesterol biosynthesis via sterol regulatory element binding transcription factors is not significantly activated in the Cyp46a1(-/-) brain to explain a compensatory decrease in cholesterol biosynthesis. Third, some of the liver X receptor target genes (Abca1) are paradoxically upregulated in the Cyp46a1(-/-) brain, possibly due to a reduced activation of the small GTPases RAB8, CDC42, and RAC as a result of a reduced phosphorylation of RAB3IP and PAK1. Fourth, the phosphorylation of many other proteins (a total of 146) is altered in the Cyp46a1(-/-) brain, including microtubule associated and neurofilament proteins (the MAP and NEF families) along with proteins related to synaptic vesicles and synaptic neurotransmission (e.g., SLCs, SHANKs, and BSN). Fifth, the extent of protein ubiquitination is increased in the Cyp46a1(-/-) brain, and the affected proteins pertain to ubiquitination (UBE2N), cognition (STX1B and ATP1A2), cytoskeleton function (TUBA1A and YWHAZ), and energy production (ATP1A2 and ALDOA). The present study demonstrates the diverse potential effects of CYP46A1 deficiency on brain functions and identifies important proteins that could be affected by this deficiency.